(untitled) (European Bison Conservation Newsletter, 2013)
The first European bison came back to the Bieszczady Mountains in 1963. The number of bison ranged between 250–300 in the last years. In March 2013 the Bieszczady bison population was estimated for 256 individuals, including 34 calves (13,3%). Natural death rate is low, and according to the collected data from the whole territory it amounts to ca. 6%. Until 2009 an involvement of forests was informal. It was only 4 years ago that Regional Directorate of State Forests in Krosno became an official attendant of the Bieszczady bison, running, supervising and coordinating all the activities of this subject in the area. It applies for decisions of keeping, catching, elimination of wisents, etc. Execution of its tasks is being aided by Commission for Protection and Breeding of E. Bison on the territory of Regional Directorate of State Forests in Krosno. This advisory body, consisting of representatives of the world of science, practitioners actually active in the area, and Regional Directorate of Environment Protection, gives advisory opinions and indicates necessary breeding and protective activities. The ongoing breeding and protective activities run by Regional Directorate of State Forests in Krosno consist of winter feeding, health and genetic monitoring, supplying the population with genetically healthy individuals from breeding stations as well as providing the local community with the knowledge concerning wisents. In the past, these activities were financed from the own means of State Forests, later on by Provincial Fund of Environment and Water Economy Protection and National Fund of Environment and Water Economy Protection. At present they are being carried out under the Project ”Protection of bison in situ in Poland – Southern part”, which is financed by European Regional Development Fund as part of Infrastructure and Environment Program (85%) and by National Fund of Environment and Water Economy Protection (15%). The whole value of the Project amounts to 3 821 599,2 PLN. The main beneficiary is Regional Directorate of State Forests in Krosno cooperating with four partners: State Forests District Offices Baligro´d, Koman´ cza, Lutowiska and Stuposiany. For 2014 the Project ”Continuation of protection of bison in situ – Southern Part” is being planned. For the time being the Project has been positively assessed at the level II – we are waiting for agreement to be signed. In the Project most of the tasks carried out so far will be continued. In the recent years extraordinary activities concerning liquidation of outbreaks of tuberculosis in one herd of the Bieszczady population were also successfully conducted. Despite numerous problems, mainly those connected with tuberculosis, the population is developing quite dynamically. The foresters, who not only carry out protective activities in the area, but also acquire financial means for them, lead the way in the protection of E. bison in the Bieszczady Mountains.